A multi-environmental time similarity theory of life prediction on coastal concrete structural durability. (4th December 2009) - Jin, Wei-Liang; Jin, Li-Bing
A multi-environmental time similarity (METS) theory for durability assessment and life prediction is presented in this paper. The METS theory is able to connect the field inspections and the indoor accelerated tests by introducing a third reference site, which has certain service life and similar aggressive environment to the study objective. Thus, the correlation between the field inspection data and indoor test results in accelerated environments could be established which enable the prediction of concrete structures service life based on indoor test results. The theoretical model and experimental method of METS are presented in details in this paper. In addition, the application of METS theory in the practical engineering project is also presented. The predictions obtained from METS theory were compared with predictions obtained by other methods. It is shown that the predictions obtained from METS theory are reasonably accurate, creditable and convictive.